1994
DOI: 10.1016/0896-6273(94)90425-1
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of rapid potassium channel inactivation by phosphorylation of the inactivation gate

Abstract: SummaryThe effect of protein kinase C (PKC) on rapid N-type inactivation of K + channels has not been reported previously. We found that PKC specifically eliminates rapid inactivation of a cloned human A-type K + channel (hKv3.4), converting this channel from a rapidly inactivating A type to a noninactivating delayed rectifier type. Biochemical analysis showed that the N-terminal domain of hKv3.4 is phosphorylated in vitro by PKC, and mutagenesis experiments revealed that two serines within the inactivation ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
124
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 52 publications
4
124
1
Order By: Relevance
“…[12][13][14] Early reports showed modulation of fast Kv3.4 channel inactivation by oxidation, phosphorylation and PIP2 in heterologous expression systems. [15][16][17][18] Demonstrating that inactivation modulation also occurs in neurons, we showed that PKC activation dramatically slows inactivation of the native Kv3.4 channel expressed in DRG nociceptors. 7 Under physiological conditions, however, Kv3.4 channel inactivation is not modulated by PIP2.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[12][13][14] Early reports showed modulation of fast Kv3.4 channel inactivation by oxidation, phosphorylation and PIP2 in heterologous expression systems. [15][16][17][18] Demonstrating that inactivation modulation also occurs in neurons, we showed that PKC activation dramatically slows inactivation of the native Kv3.4 channel expressed in DRG nociceptors. 7 Under physiological conditions, however, Kv3.4 channel inactivation is not modulated by PIP2.…”
Section: Introductionmentioning
confidence: 95%
“…This is potentially significant because, in addition to phosphorylation, oxidation also eliminates Kv3.4 Ntype inactivation. 16,17 If the neuron is dialyzed with an oxidizing or PKC activating intracellular solution in the whole-cell configuration, Kv3.4 channels might switch from A-type to delayed rectifiertype. Further experimentation is, however, necessary to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine kinase activation by G protein-coupled receptors (19) also suppresses delayed rectifying potassium channels by phosphorylation of a tyrosine residue in the amino terminus of Kv1.2 (20). Similarly, phosphorylation of serine residues in the amino terminus of a different delayed rectifying potassium channel Kv3.4 causes channel inactivation (21). Additionally, tyrosine phosphorylation of other potassium channels may regulate neuronal excitability.…”
mentioning
confidence: 99%
“…Other Shaker-related K V channels, e.g., Shaker itself, K V 1.4, and K V 3.4, express outward currents that rapidly inactivate within milliseconds because of the presence of an amino-terminal inactivation domain (Hoshi et al, 1990). It was shown that phosphorylation of the amino-terminal inactivation domain of K V 3.4 channels by protein kinase C (PKC) completely eliminated N-type inactivation (Covarrubias et al, 1994). Also, dephosphorylation of a modulatory C-terminal site of Drosophila Shaker channels considerably slowed the inactivation rate (Drain et al, 1994).…”
mentioning
confidence: 99%
“…Covarrubias et al (1994) showed for the cloned human A-type K V channel, hK V 3.4 that PKC-dependent phosphorylation within the inactivation domain completely eliminates N-terminal inactivation. Conversely, Drain et al (1994) demonstrated for Shaker K V channels that the phosphorylation of a C-terminal consensus site by PKA induces an acceleration of the macroscopic and microscopic transition from the open channel into the inactivated state.…”
mentioning
confidence: 99%